SIGNIFICANT CONTRIBUTIONS OF OIL PALM PLANTATION TOWARDS SUSTAINABLE DEVELOPMENT GOALS IN RURAL LIVELIHOOD - Judijanto, Loso (Anais New Science Publishers | Editora Impacto, 2025)
The growing global emphasis on Sustainable Development Goals (SDGs) has intensified interest in understanding how agricultural sectors contribute to rural livelihoods. The objective of this research is to analyze the extent to which oil palm cultivation facilitates the attainment of SDGs in countryside communities. Employing a qualitative literature review methodology, the research synthesizes findings from over 80 peer-reviewed articles, policy reports, and institutional publications to provide an in-depth analysis. Data were systematically collected through comprehensive database searches focusing on relevant secondary sources. Thematic content analysis was utilized to interpret and categorize the data based on economic, social, environmental, and governance aspects. the study highlights the vital role of oil palm estates in enhancing the economic livelihoods of rural populations, employment, food security, education, and infrastructure development, even as it brings about environmental issues like the clearing of forests and the degradation of water quality. Sustainable management practices and effective governance frameworks were identified as crucial factors in maximizing benefits and minimizing negative impacts. In conclusion, oil palm cultivation significantly contributes to multiple SDGs when integrated within responsible and inclusive policy environments. Upcoming studies are encouraged to conduct long-term evaluations and engage local stakeholders through participatory techniques to better understand the connection between palm oil activities and sustainable development in village-level contexts.